Effects of the reactive metabolite methylglyoxal on cellular signalling, insulin action and metabolism - What we know in mammals and what we can learn from yeast - Zemva, Johanna; Pfaff, Daniel; Gröner, Jan; Fleming, Thomas; Herzig, Stephan; Teleman, Aurelio A.; Nawroth, Peter Paul; Tyedmers, Jens (Experimental and clinical endocrinology & diabetes, 2019)
Levels of reactive metabolites such as reactive carbonyl and oxygen species are increased in patients with diabetes mellitus. The most important reactive dicarbonyl species, methylglyoxal (MG), formed as by-product during glucose metabolism, is more and more recognized as a trigger for the development and progression of diabetic complications. Although it is clear that MG provokes toxic effects, it is currently not well understood what cellular changes MG induces on a molecular level that may lead to pathophysiological conditions found in long-term diabetic complications. Here we review the current knowledge about the molecular effects that MG can induce in a cell. Within the mammalian system, we will focus mostly on the metabolic effects MG exerts when applied systemically to rodents or when applied in vitro to pancreatic β-cells and adipocytes. Due to the common limitations associated with complex model organisms, we then summarize how yeast as a very simple model organism can help to gain valuable comprehensive information on general defence pathways cells exert in response to MG stress. Pioneering studies in additional rather simple eukaryotic model organisms suggest that many cellular reactions in response to MG are highly conserved throughout evolution.
08. Februar 2018 (online)
Gesehen am 28.01.2020